Penerapan recipe cost calculator untuk perhitungan Harga Pokok Produksi (HPP) Ben Coffee - Sulastri, Heni (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2025)
The calculation of cost of goods manufactured plays a crucial role in maintaining the sustainability of a business, especially in the face of increasing business competition and rising production costs. Setting the right selling price is a challenge for business owners, especially in the tender process to prospective clients, because mistakes in determining prices can risk causing losses. This study aims to calculate the cost of goods produced at Ben Coffee by applying the Recipe Cost Calculator. The research method used is descriptive with a qualitative approach, and adopts observation, interview, and documentation techniques in data collection. Data analysis was carried out through three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that the application of Recipe Cost Calculator allows Ben Coffee to calculate the cost of goods produced more accurately, efficiently, and systematically. In addition, this method helps business owners in setting a more appropriate selling price and in knowing the amount of profit and potential losses that can occur.